On Farm Assessment of INM Techniques on Soil Health and Yield of Rice in Sahibganj, Jharkhand - Jha, Amrit Kumar; Kumar, Anjani; Mehta, Birendra Kumar; Kumari, Maya; Chatterjee, Kaushik (Indian Journal of Extension Education, 2021)
On-farm trial was conducted to assess the Integrated Nutrient Management (INM)Â techniques on yield of rice and soil health after harvest during 2018-19 and 2019-20 at ten locations. The result of three treatments viz. Farmerâ€™s Practice, Technology Option 1 andÂ Technology Option 2 indicated that TO1 and TO2 significantly increased the yield and yield attributing characters over farmerâ€™s practice (FP). Significantly high yield of rice grain (41.2 q per ha) was recorded with INM techniques. The data on available N, P and KÂ status of soil after harvest of rice crop was significantly higher under TO2 as compared to FP. Highest net-return (Rs. 44,214 per ha) with B:C ratio of 2.44 was reported underÂ TO2. INM techniques also resulted in lowest technology gap (8.78 q per ha) and technology index (17.56%) over other treatments which suggests itâ€™s feasibility at farmerâ€™s field.